PENGARUH DOSIS UREA DALAM AMONIASI DAUN NENAS VARIETAS Smooth cayene TERHADAP KADAR BAHAN KERING, ABU, DAN SERAT KASAR - Febri Puspitasari; Farida Fathul; Syahrio Tantalo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Lampung Province as a livestock area resulted in needed for food supplies that available onfollow throughout the years, so the attempted of feed based on agriculture waste industry, one of themis pineapple leaves. However, the pineapple leaves in a fresh condition have a high crude fiber contentand low protein content. Therefore, the pineapple leaves will be ammoniateed with urea addition atdifferent dosages in order to lessen the high fiber content. This study aimed to determine the effect ofurea and the best dosage on ammoniation of pineapple leaves of Smooth cayene variety onorganoleptic (color, texture, smell), dry matter, ash, and crude fiber content.This study was held in the Laboratory of Animal Nutrition and Feed, Department of AnimalHusbandry, Faculty of Agriculture, Lampung University and pineapple leaves samples obtained fromPT Great Giant Pineapple, Terbanggi Besar, Central Lampung. The treatments using a CompletelyRandomized Design (CRD) with four treatments and three replications. The treatments consist of ureaaddition at a dosage of 0%; 1,5%; 3% and 4,5%. The observation data were analyzed by usingvariance analysis with significant level of 5% and or 1%, and will be followed by the Least SignificantDifference test (LSD) if the value of the variance analysis showed the significant result.The results of this study showed that urea addition at different dossages had no significant effect(P>0,05) on organoleptic (color, texture, smell) and crude fiber content of pineapple leaves, butsignificantly (P<0,05) to the ash content and was highly significant (P<0,01) to the dry matter. Thebest treatment on ammoniation of pineapple leaves of Smooth cayenne variety is urea addition atdosage of 1,5%.